Caracterização do amido da araruta tipos seta e redonda, visando utilização na indústria de alimentos - Cunha, Amanda Logato (2016)
Starch and their derivatives are used in almost all industrial sectors. In the food industry, can be used as basic ingredients of products or additives, improving products, their presentation or conservation. Tropical countries such as Brazil, have great variety of starchy species that could replace modified starches in processed foods. In this work, starches of the redonda arrowroot and seta arrowroot were analyzed and compared, to be carried out the study of its physicochemicals, thermals, opticals and rheologicals characteristics, and the verification of their applicability in the food industry. The work consisted in the determination of moisture, protein, ethereal extract, crude fiber, ash, glycidic fraction, pH, titratable acidity, total starch, phosphorus content, pasting properties, ability to absorb water and oil, swelling power and starch solubilization rate, image analysis, FTIR, X-ray diffraction, thermal properties (DSC and TG / DTA), paste clarity. The results of the centesimal composition, the swelling power and solubility, water absorption capacity and oil and paste clarity were analyzed by the observation means and standard deviations of three replicates. The centesimal composition of the two starches showed high crude fiber content, which may be attributed to the advanced stage of maturity of arrowroot rhizomes. The pH value was below, while the acidity was in agreement with the literature. The two starch contents were very close, being within the limit, while phosphorus contents were higher than those found in other studies. Both arrowroot starch showed weakness at high temperatures and mechanical agitation; less resistance to dissociation of hydrogen bonds and ease of expansion; high water retention capacity of the granules before the rupture; and high viscosity end. The starch of seta arrowroot proved to be more tendency to retrograde the redonda arrowroot. Low values for capacity of water absorption, swelling power and solubility index were found, besides high values for oil absorption. Starch granules showed heterogeneous size, oval and ellipsoid appearance and crystallinity of type C. Main chemical groups present in polysaccharides were found. The redonda arrowroot presented Tonset 299°C and 49% mass loss during the degradation step, while seta arrowroot presented Tonset 293°C and 52% mass loss. The gelatinization range for the redonda arrowroot starch was 45.87°C to 61.37°C with enthalpy of 12.56 J g-1, and gelatinization range of seta arrowroot starch was 46.83°C to 62.10°C, and enthalpy of 15.73 J g-1. The two pastes of starches have low transparency, and can be used in sauces and in the production of puddings and ready desserts, and baked products.